The initiation of transverse matrix cracking and longitudinal matrix cracking in composite cross-ply laminates: Analysis of a damage criterion. Issue 1 (31st December 2016) - Rebière, Jean-Luc
Abstract: The results of stress field distribution in damage cross-ply laminates prompt us to elaborate an energy criterion. This criterion is based on the partial parts's computation of the strain energy release rate associated with each damage type and for all loading modes. In the related criterion, based on the linear fracture approach, several hypotheses are used to simplify the damage criterion. The main objective with this approach is to estimate the onset of transverse and longitudinal cracking mechanisms and the development of the damage. Only results from numerical simulations are proposed for one material; numerous numerical simulations, with other materials and laminate architectures, give similar evolutions of matrix cracking damage.